Liquidity Risk Factors and Stock Returns’ Dynamic Relation in Bullish and Bearish Condition of Indonesia and Japan’s Capital Market - Igo Febrianto; Erni Ekawati (The Indonesian Journal of Accounting Research, 2015)
Abstract: The purpose of this research is to examine the dynamic relation between liquidity as a risk factor and stock returns in different market conditions (i.e., bullish and bearish) and two different market developments (emerging and developed). Several measures of liquidity levels and variability level of liquidity are employed. In this research, Indonesia is chosen as a sample of a country with an emerging economy, while Japan is selected as a sample of a country with a developed economy. This study shows that liquidity is an essential factor affecting portfolio returns. In this research, liquidity is found to affect bullish and bearish stock market condition. Nonetheless, liquidity risk factors found to be incapable of explaining characteristic differences between emerging and developed stock market. On the other hand, this study shows that there is a correlation between liquidity effect and some liquidity categories in the developed portfolios. These findings highlight future avenues of accounting research, particularly in the area of liquidity risk factors and corporate’s information quality as well as transparency.Abstract: Tujuan dari penelitian ini adalah untuk menguji hubungan dinamis antara likuiditas sebagai faktor risiko dan pengembalian saham dalam kondisi pasar yang berbeda (yaitu, bullish dan bearish) dan dua perkembangan pasar yang berbeda (muncul dan dikembangkan). Beberapa ukuran tingkat likuiditas dan tingkat variabilitas likuiditas digunakan. Dalam penelitian ini, Indonesia dipilih sebagai sampel suatu negara dengan ekonomi yang sedang bangkit, sedangkan Jepang dipilih sebagai sampel suatu negara dengan ekonomi yang dikembangkan. Studi ini menunjukkan bahwa likuiditas merupakan faktor penting yang mempengaruhi pengembalian portofolio. Dalam penelitian ini, likuiditas ditemukan mempengaruhi kondisi pasar saham bullish dan bearish. Meskipun demikian, faktor risiko likuiditas ditemukan tidak mampu menjelaskan perbedaan karakteristik antara pasar saham yang muncul dan berkembang. Di sisi lain, penelitian ini menunjukkan bahwa ada korelasi antara efek likuiditas dan beberapa kategori likuiditas dalam portofolio yang dikembangkan. Temuan ini menyoroti berbagai penelitian akuntansi di masa depan, khususnya di bidang faktor risiko likuiditas dan kualitas informasi perusahaan serta transparansi.